Análisis de la afluencia de esquiadores a 3 estaciones de esquí del Pirineo aragonés en relación con la disponibilidad de nieve, el calendario vacacional y las condiciones meteorológica - Gilaberte Búrdalo, María; López Moreno, Juan Ignacio; López Martín, Fernándo Germán (Geographicalia, 2021)
This study analyzes the daily attendance data of skiers in three ski resorts in the Aragonese Pyrenees and their relationship with the availability of snow, the weather and the holiday calendar during the period 2003-2013. The results show great interannual variability in the length of the season and in the attendance of skiers. The stations were open an average of 130 days per season and the start and end dates are highly conditioned by the holiday calendar rather than by snow-meteorological factors. Weekends have twice as many skiers as a weekday. Elements such as the low availability of snow and wind conditions had the greatest impact on the attendance of skiers as well as the closure of the stations. The percentage of open tracks is also correlated with attendance; there were three times as many skiers when 75% of the ski slopes were open relative to the days when 25% were open.